Atributos de calidad del servicio y satisfacción del cliente en las nuevas cadenas de supermercados de la ciudad de Trujillo; sugerencias estratégicas de mejora, 2008-2009 - Tandaypan Salazar, Jorge Luis (2010)
This research work had as a main objective to identify and analyze the main "Attributes of service quality and its relationship with the degree of customer satisfaction in the new supermarket chains established in the city of Trujillo 2008-2009." To achieve this goal, it initially identifies the quality of services provided in a general way and the general satisfaction experienced by customers when they go to supermarkets according to their degree of importance. The study was correlational-descriptive and the performed bibliographic review allowed to give theoretical and philosophical underpinnings to it. The sample was composed by 523 guests who attended the new supermarkets. We used a questionnaire that permitted us to identify the specific attributes and their direct relationship with the satisfaction of customers visiting the new supermarkets, which was validated by an expert group to achieve a higher degree of validity and reliability in the development of research. The analysis of the results allowed to identify the best specific quality attributes such as clear indication of prices, quality and uses of products and services, the shelves are always full (of products/brands preferred by customers), services begin and conclude at the promised time, the sold brands are well known and of good quality, the attention hours are convenient for customers, the adequate internal design allows customers to go everywhere freely, employees are concerned about the service needs of customers, customers feel secure about their transactions, employees are able to manage complaints directly and immediately, facilities and ambience (sound, scent and temperature) and lighting to exhibit the products attractively are visually good and fair; which are directly related to customer satisfaction in the new supermarket chains, besides customers feel mainly satisfied and very satisfied with their experiences of visiting the new supermarkets.